Síntese e caracterização de aerogéis anfifílicos à base de acrilamida e óleo de girassol destinados à remoção de petróleo - Freitas, Williane da Silva (2017)
Due to the increasing exploration of oil, high volumes of this raw material have often been transported by sea. Consequently, several accidents involving its spill have been reported, wich affects significantly the fauna and flora, besides the atmosphere. Traditionaly, equipment and materials for containment and mechanical removal of spilled oil are used, such as: spillways and skimmers, of low selectivity and removal efficiency (from 10 to 15 %), and sorbents such as blankets and barriers. In order to contribute to an environmentally less aggressive alternative that combine removal efficiency and lower cost of production, is proposed the synthesis of chemically crosslinked amphiphilic polymer aerogels derived from acrylamide (hydrophilic monomer) and refined sunflower oil (SO). Aerogels are materials wich can be derived from gels, whose continuous phase is replaced by air during a specific drying process. Among the most characteristic properties, the low density and high surface area stand out. The amphiphilic polymers are structurally constituted by hydrophilic and hydrophobic segments, which confers them the ability to interact with polar and nonpolar means. In order to obtain aerogels, the micellar copolymerization technique was adopted, in which hydrophilic monomers are polymerized in the aqueous phase (continuous) which are responsible for the incorporation of the hydrophobic species contained in the micelles formed by the action of a surfactant, resulting in formation of a copolymer. The aerogels synthesis and optimization were based on variations of: SO, surfactant, crosslinker and initiators. The physicochemical analyzes of SO have shown a high content of unsaturated fatty acid derivatives, indicating their potential as a source of reactive lipophilic species. Its physical and chemical characteristics are in compliance with the standards established by regulatory bodies. The FTIR and CHNS analysis reveal the presence of SO in the aerogels polymer matrix. The sorption tests using hexane over 2 h allowed to identify better performance for the aerogel AMOG34-2R:8I-30, synthesized from 34,4 % m/m of SO, 0,4 mol % of crosslinker, 8 times the starting amount “I” of the initiators and 30 times the CMC of SDS. From UV-Vis study was determined the content around 7 % m/m of hydrophobic species related to acrylamide. The images obtained by SEM revealed a macroporous structure that influenced the low density (0,032 g.cm -3 ) obtained for the aerogel. In the sorption tests using hexane, octane, toluene, gasoline, kerosene and diesel, were observed remarkable performances with some higher values than those reported in the literature to advanced sorbent materials. The sorption capacity (SC) according to the long-term test established by ASTM-F726-12 using pump oil and petroleum, were about 58 and 115 % higher than that of commercial PP blanket. In simulated sea water and distilled water the SC was lower than that observed in petroleum, to the saturation time of 15 min. The optimized aerogel showed a notable potential for the proposed application and superior performance to one of the most used 100 % synthetic sorbent materials.